Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-69045
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Film Cooling Performance on a Turbine Vane Suction Side Due to Surface Roughness

Abstract: After an extended period of operation, the surfaces of turbine airfoils become extremely rough due to deposition, spallation, and erosion. The rough airfoil surfaces will cause film cooling performance degradation due to effects on adiabatic effectiveness and heat transfer coefficients. In this study, the individual and combined effects of roughness upstream and downstream of a row of film cooling holes on the suction side of a turbine vane have been determined. Adiabatic effectiveness and heat transfer coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Roughness effects on the suction side of a simulated vane were investigated by Bogard et al 56 and Rutledge et al 57 Roughness upstream and downstream of a row of cylindrical holes was investigated independently, using an array of conical elements 0.25d in height. This roughness configuration was estimated to have an equivalent sand grain roughness Reynolds number of Re k ≈ 50 based on the boundary-layer flow approaching the coolant holes.…”
Section: H Surface Roughnessmentioning
confidence: 99%
“…Roughness effects on the suction side of a simulated vane were investigated by Bogard et al 56 and Rutledge et al 57 Roughness upstream and downstream of a row of cylindrical holes was investigated independently, using an array of conical elements 0.25d in height. This roughness configuration was estimated to have an equivalent sand grain roughness Reynolds number of Re k ≈ 50 based on the boundary-layer flow approaching the coolant holes.…”
Section: H Surface Roughnessmentioning
confidence: 99%
“…This is because of the erosion, spallation and deposition as illustrated in Figure 22. Previous works on surface roughness done by Bogard et al [47] and Rutledge et al [48], though limited to their narrow set of test conditions, revealed that a rougher airfoil surface will lead to early boundary layer transition making it thicker which results in turbulent mixing in the boundary layer. Shown in Figure 24 it can be seen that the rougher configuration (gray) have lower effectiveness values at BR's of 0.3 and 0.7.…”
Section: The Effect Of Surface Roughness On Film Cooling Effectivenessmentioning
confidence: 98%
“…The occurrence of these structures depends on local details of the geometry and flow conditions. Rutledge et al (2005) investigated the influence of surface roughness on the heat transfer. Upstream roughness enlarges the boundary layer thickness by a factor of three.…”
Section: Introductionmentioning
confidence: 99%